2017
DOI: 10.1016/j.sdj.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of dentinal tubules with 2% Chlorhexidine gel, Calcium hydroxide and herbal intracanal medicaments against Enterococcus faecalis : An in-vitro study

Abstract: 2% Chlorhexidine gel gave the best results. Among the herbal extracts Propolis and Curcuma longa hold a promising future but to implement their use as sole intracanal medicaments clinically, further in vivo and long term studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 24 publications
1
29
0
3
Order By: Relevance
“…The proficiency of E. faecalis to infiltrate dentinal tubules even up to a depth of 1000 µm is accredited to efaA and ace, bacterial adhesion factors. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proficiency of E. faecalis to infiltrate dentinal tubules even up to a depth of 1000 µm is accredited to efaA and ace, bacterial adhesion factors. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were irrigated with 10 mL of sterile saline at the end of 21 days to remove the incubation broth. [ 3 ] They were assigned into the remaining groups.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The results of colony count showed that H-Av mixture at a concentration of 25% completely inhibited the growth of the studied bacteria. In studies examining the antibacterial effect of Aloe vera and chlorhexidine against E.faecalis, chlorhexidine has shown better results than aloe vera (24)(25)(26). In the agar well diffusion test, H-Av mixture at a concentration of 25% did not show significant difference in the diameter of inhibitory zone compared to 2% chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…Canal lumen 57741:9165 + 4885:35226 0.02 Dentinal chips 64333:3333 + 6468:72819 7 BioMed Research International intracanal medicaments [35,[77][78][79], a more significant effort is done to develop materials that can eliminate EF from the root canal system completely.…”
Section: S3mentioning
confidence: 99%